Suppression of the necroptotic cell death pathways improves survival in Smn2B/− mice - Chehade, Lucia; Deguise, Marc-Olivier; De Repentigny, Yves; Yaworski, Rebecca; Beauvais, Ariane; Gagnon, Sabrina; Hensel, Niko; Kothary, Rashmi (Frontiers in Cellular Neuroscience, 2022)
Spinal muscular atrophy (SMA) is a monogenic neuromuscular disease caused by low levels of the Survival Motor Neuron (SMN) protein. Motor neuron degeneration is the central hallmark of the disease. However, the SMN protein is ubiquitously expressed and depletion of the protein in peripheral tissues results in intrinsic disease manifestations, including muscle defects, independent of neurodegeneration. The approved SMN-restoring therapies have led to remarkable clinical improvements in SMA patients. Yet, the presence of a significant number of non-responders stresses the need for complementary therapeutic strategies targeting processes which do not rely solely on restoring SMN. Dysregulated cell death pathways are candidates for SMN-independent pathomechanisms in SMA. Receptor-interacting protein kinase 1 (RIPK1) and RIPK3 have been widely recognized as critical therapeutic targets of necroptosis, an important form of programmed cell death. In addition, caspase-1 plays a fundamental role in inflammation and cell death. In this study, we evaluate the role of necroptosis, particularly RIPK3 and Caspase-1, in the Smn2B/- mouse model of SMA. We have generated a triple mutant (TKO), the Smn2B/-;Ripk3-/-;Casp1-/- mouse. TKO mice displayed a robust increase in survival and improved motor function compared to Smn2B/- mice. While there was no protection against motor neuron loss or neuromuscular junction pathology, larger muscle fibers were observed in TKO mice compared to Smn2B/- mice. Our study shows that necroptosis modulates survival, motor behavior and muscle fiber size independent of SMN levels and independent of neurodegeneration. Thus, small-molecule inhibitors of necroptosis as a combinatorial approach together with SMN-restoring drugs could be a future strategy for the treatment of SMA.